Above‐ and below‐ground assessment of carabid community responses to crop type and tillage. (21st July 2020) - Jowett, Kelly; Milne, Alice E.; Garrett, Dion; Potts, Simon G.; Senapathi, Deepa; Storkey, Jonathan
Abstract: Carabid beetles are major predators in agro‐ecosystems. The composition of their communities within crop environments governs the pest control services they provide. An understudied aspect is the distribution of predacious carabid larvae in the soil. We used novel subterranean trapping with standard pitfall trapping, within a multi‐crop rotation experiment, to assess the responses of above‐ and below‐ground carabid communities to management practices. Crop and trap type significantly affected pooled carabid abundance with an interaction of the two, the highest numbers of carabids were caught in subterranean traps in barley under sown with grass. Trap type accounted for the most variance observed in carabid community composition, followed by crop. Tillage responses were only apparent at the species level for three of the eight species modelled. Responses to crop type varied by species. Most species had higher abundance in under‐sown barley, than grass, wheat and barley. Crop differences were greater in the subterranean trap data. For predaceous larvae, standard pitfalls showed lowest abundances in under‐sown barley, yet subterranean traps revealed abundances to be highest in this crop. Comprehensive estimation of ecosystem services should incorporate both above‐ and below‐ground community appraisal, to inform appropriate management. Abstract : Crop and trap type affect pooled carabid abundance, the highest numbers were caught in subterranean traps in barley under sown with grass. Responses to crop type varied by species. Subterranean trapping revealed below‐ground movements of carabids that may be missed with standard pitfall trapping alone. Trap type accounted for the most variance observed in carabid community composition. Subterranean traps were more efficient in trapping carabid larvae. For predaceous larvae standard pitfalls showed lowest abundances in under‐sown barley, yet subterranean traps revealed highest abundances in this crop.